Application of Soft System Methodology for Modelling Institutional Strengthening of Salt Farmers - Riza, Faisol; Wijaya, Chandra (Technium Social Sciences Journal, 2022)
Salt farmers (smallholders) are the main actors in the production cycle of the national salt supply chain. However, they still face various problems regarding production technology, productivity, quality, market prices, product absorption by industry, access to capital, and incentives. Strengthening their institutional capacity requires collaboration and support from the government and other actors along the supply chain. This study aims to develop a model of institutional strengthening of salt farmers by applying a soft systems methodology. The institutional strengthening model was developed in three forms, i.e., the establishment of a salt farming corporation, the formation of cooperatives, and the revitalization of the salt farmer association. Various individual actors are involved, assessed, and then integrated into this model. The suggested strengthening model involves cooperatives and/or BUMDes (village-owned enterprises), farmer groups, and processing factories supported by government and financial institutions with partnership programs.